Vascular Targets for the Treatment of Portal Hypertension - Brusilovskaya, Ksenia; Königshofer, Philipp; Schwabl, Philipp; Reiberger, Thomas (Seminars in Liver Disease, 2019)
Portal hypertension is the main driver for severe complications in patients with liver cirrhosis. With improved understanding of molecular pathways that promote hepatic vascular remodeling, vasoconstriction, and sinusoidal capillarization potential vascular targets for the treatment of portal hypertension have been identified. Inhibition of vascular endothelial and platelet-derived growth factors–driven angiogenesis has been shown to reduce portal pressure and decrease hepatic inflammation. Angiopoietin/Tie signaling represents additional promising vascular targets in liver disease. The eNOS-NO-sGC-cGMP pathway modulates sinusoidal vasoconstriction and capillarization. Nuclear farnesoid X receptor (FXR) agonists decrease intrahepatic vascular resistance by inhibition of fibrogenesis and sinusoidal remodeling. Statins ameliorate endothelial dysfunction, decrease portal pressure, and reduce fibrogenesis. Anticoagulation with low-molecular heparin or anti-Xa inhibitors improved portal hypertension by deactivation of hepatic stellate cells and potentially via reduction of sinusoidal microthrombosis. This review summarizes important vascular targets for treatment of portal hypertension that have shown promising results in experimental studies.
Keywords: portal hypertension; fibrosis; angiogenesis; sGC; FXR; anticoagulation; statins